The correlation between maternal education and infant growth and development aged 0-6 months was studied at Pratama Arapenta clinic - Tiarnida Nababan; Purba, Resmiana; Lumban gaol, Resnauli; Hasibuan, Revina Oktania; Ria Agustina (Sean Institute, 2024)
Baby massage is very useful in optimizing the growth and development of babies/children, including increasing food absorption so that babies are hungry faster and babies will suckle more often to their mothers so that they can increase body weight in babies.The Aim : This study aims to analyze the effect of infant massage on increasing body weight in infants. Method: The research method used is quantitative research methods, using Quasi-experiment design with Pretest design - Postest design. The population in this study were infants aged 2-12 months in the village of Giripurwo, Wonogiri Jurnal Kebidanan Indonesia. Vol 10 No 1. Januari 20 (12 – 18)13 District, which numbered 30 people. The sample in this study was infants aged 2 - 12 months in the village of Giripurwo, the sample in this study was the total population. Data analysis in this study with univariate analysis and bivariate analysis. Univariate analysis is gender, an age of the baby. Bivariate analysis to prove the effect of infant massage on increasing infant weight before and after treatment using the Wilcoxon Test. Measurements of respondents' weight in the intervention group were carried out 2 times, first when taking data before a baby massage, and finally when after a month a baby massage was carried out. Results: P-Value = 0,000 (fter a month a baby massage was carried out. Conclusion: there is the effect of infant massage on increasing body weight in infants.